Analysis Of Magnetic Materilas - Ataxonova Sayyora Koraboyevna; Abdug'aniyeva Xurshida Raximjon qizi; Shavkatov Ulug'bek Murodjon o'g'li (Zien Journals, 2022)
This article gives you a brief overview on magnetic resonance imaging. The properties, mechanical properties and applications of magnetic materials are widely covered.
Keywords: Paramagnetic; thermomagnetic; manganese-zinc; austenite